1904 Ky. Acts 150-51, An Act Creating the Offices of Fish and Game Wardens and Defining the Powers and Duties and Fixing the Compensation of such Officers, and for the Further Protection and Preservation of Fish, Game and Birds in the State of Kentucky, ch. 68, § 3. - (:unkn) unknown (General Publisher, 1904)
Game wardens . . . may arrest on sight and without warrant any person detected by them in the act of violating any such law; they shall have the same right as sheriffs to require aid in executing any process or in arresting without process any person found by them in the act of violating any of said laws; and they shall have authority to seize without process; and birds, fish or game then found in the possession of any such person, together with the guns, nets, seines, traps or other devices, with which the same were taken or killed, and destroy or confiscate such guns, nets, seines, traps or other devices, and forthwith convey such offender before a court or magistrate . .
--
Keywords: HUNTING REGULATION